Hypoxemia Index Associated with Prehospital Intubation in COVID-19 Patients - Jouffroy, Romain (J Clin Med, 2020)
Background: There exists a need for prognostic tools for the early identification of COVID-19 patients requiring prehospital intubation. Here we investigated the association between a prehospital Hypoxemia Index (HI) and the need for intubation among COVID-19 patients in the prehospital setting. Methods: We retrospectively analyzed COVID-19 patients initially cared for by a Paris Fire Brigade advanced life support (ALS) team in the prehospital setting between 8th March and 18th April of 2020. We assessed the association between HI and prehospital intubation using receiver operating characteristic (ROC) curve analysis and logistic regression model analysis after propensity score matching. Results are expressed as odds ratio (OR) and 95% confidence interval (CI). Results: We analyzed 300 consecutive COVID-19 patients (166 males (55%); mean age, 64 ± 18 years). Among these patients, 45 (15%) were deceased on the scene, 34 (11%) had an active care restriction, and 18 (6%) were intubated in the prehospital setting. The mean HI value was 3.4 ± 1.9. HI was significantly associated with prehospital intubation (OR, 0.24; 95% CI: 0.12–0.41, p < 10(−3)) with a corresponding area under curve (AUC) of 0.91 (95% CI: 0.85–0.98). HI significantly differed between patients with and without prehospital intubation (1.0 ± 1.0 vs. 3.6 ± 1.8, respectively; p < 10(−3)). ROC curve analysis defined the optimal HI threshold as 1.3. Bivariate analysis revealed that HI <1.3 was significantly, positively associated with prehospital intubation (OR, 38.38; 95% CI: 11.57–146.54; p < 10(−3)). Multivariate logistic regression analysis demonstrated that prehospital intubation was significantly associated with HI (adjusted odds ratio (ORa), 0.20; 95% CI: 0.06–0.45; p < 10(−3)) and HI <3 (ORa, 51.08; 95% CI: 7.83–645.06; p < 10(−3)). After adjustment for confounders, the ORa between HI <1.3 and prehospital intubation was 3.6 (95% CI: 1.95–5.08; p < 10(−3)). Conclusion: An HI of <1.3 was associated with a 3-fold increase in prehospital intubation among COVID-19 patients. HI may be a useful tool to facilitate decision-making regarding prehospital intubation of COVID-19 patients initially cared for by a Paris Fire Brigade ALS team. Further prospective studies are needed to confirm these preliminary results.